Plan de mejoramiento para el departamento de logística de la empresa SALUD-PRO S.A. en la ciudad de Cali (2014)
The company aware of this need, has aimed at achieving the quality of their services and this paper a discussion of the diagnosis of the current situation of the Department of Logistics and activities to be developed to achieve. The company is presented deficiencies in logistics department this makes the company does not take into account a strategy to ensure better organization in this area, which can further increase the cost of service, affecting only company. It is therefore necessary for the company, implement a plan for improvement in the area of logistics, because this way the company ceased to have losses in the medium and long term. To make such investigation Three types of interviews and a checklist in order to identify factors to analyze the area was used as a tool for gathering information. Additional monitoring conducted them to the journeys made by the winery and office assistant in collecting orders 6 different lines of hospital supplies sold by the company. This reflects the company we did not have to clear the storage of products, the staff did not have the proper training guidelines, there were no operating manuals and other items. This requires an improvement plan and an action plan valued, in order to make improvements and be financially leveraged presented.